2021
DOI: 10.3390/ijms22136808
|View full text |Cite
|
Sign up to set email alerts
|

Photoinactivation of Pseudomonas aeruginosa Biofilm by Dicationic Diaryl-Porphyrin

Abstract: In recent years, antimicrobial photodynamic therapy (aPDT) has received increasing attention as a promising tool aimed at both treating microbial infections and sanitizing environments. Since biofilm formation on biological and inert surfaces makes difficult the eradication of bacterial communities, further studies are needed to investigate such tricky issue. In this work, a panel of 13 diaryl-porphyrins (neutral, mono- and di-cationic) was taken in consideration to photoinactivate Pseudomonas aeruginosa. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…The antibacterial photodynamic activity of GaPP and GaPP-LCNP was evaluated against P . aeruginosa (PAO1) in planktonic culture, as previously reported [ 17 , 18 ] with appropriate modifications. Briefly, an overnight culture of P .…”
Section: Methodsmentioning
confidence: 99%
“…The antibacterial photodynamic activity of GaPP and GaPP-LCNP was evaluated against P . aeruginosa (PAO1) in planktonic culture, as previously reported [ 17 , 18 ] with appropriate modifications. Briefly, an overnight culture of P .…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, strong binding can have negative consequences, as seen among the 13 diaryl-porphyrins (neutral, mono-and di-cationic) tested on P. aeruginosa; it turned out, as expected, that all the cationic ones strongly bind to the bacterial cell, but some of them were intrinsically toxic and were thus excluded from further studies [137]. A cationic porphyrin that did not show intrinsic toxicity, dicationic diaryl porphyrin with two benzyl groups attached to nitrogen atoms of two pyridyl substituents on the porphyrin, was chosen as the most promising against P. aeruginosa PAO1 biofilm [137]. This PS was applied with blue light (410 nm; 30 J/cm 2 ) against biofilms formed by two clinical isolates, among which BT1 clinical isolate formed a biofilm with very high biomass value, and the PS inhibited biomass adhesion for all tested strains [137].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 82%
“…A cationic porphyrin that did not show intrinsic toxicity, dicationic diaryl porphyrin with two benzyl groups attached to nitrogen atoms of two pyridyl substituents on the porphyrin, was chosen as the most promising against P. aeruginosa PAO1 biofilm [137]. This PS was applied with blue light (410 nm; 30 J/cm 2 ) against biofilms formed by two clinical isolates, among which BT1 clinical isolate formed a biofilm with very high biomass value, and the PS inhibited biomass adhesion for all tested strains [137]. Together with light, the PS caused a significant reduction of the adherent population and biomass, as well as planktonic population, while for the mature biofilm (24 h old), there was a mild effect (2-log reduction) on all cells in the biofilm [137].…”
Section: Pseudomonas Aeruginosamentioning
confidence: 99%
“…Porphyrin PSs have been widely tested in the treatment of Pseudomonas aeruginosa, another Gram-negative OPPP. Orlandi et al recently tested the effects of a group of 13 diaryl porphyrins on biofilm formation and eradication of biofilm mass [36]. It was shown that diaryl porphyrins bearing two positively charged pyridyl groups on the opposite side of the porphyrin core have the highest antibiofilm properties and can inhibit the biofilm formation and have a mild effect on the formed biofilm [36].…”
Section: Pneumophila Biofilm Destruction In Different Water Hardnessmentioning
confidence: 99%
“…Orlandi et al recently tested the effects of a group of 13 diaryl porphyrins on biofilm formation and eradication of biofilm mass [36]. It was shown that diaryl porphyrins bearing two positively charged pyridyl groups on the opposite side of the porphyrin core have the highest antibiofilm properties and can inhibit the biofilm formation and have a mild effect on the formed biofilm [36]. The authors presumed that the highest antibiofilm properties are due to the positive charge of the pyridyl groups being delocalized and directly coordinated with the tetrapyrrole system of porphyrin.…”
Section: Pneumophila Biofilm Destruction In Different Water Hardnessmentioning
confidence: 99%